DRIVERS AND ENABLERS OF AFFECTIVE COMMITMENT: STUDY OF HIGHER EDUCATIONAL INSTITUTIONS IN INDIA - Sabbarwal, Taruna; Sharma, Dr. Saumya Kapoor; Rai, Dr. Anjali; Mishra, Dr. Amar Kumar (The journal of contemporary issues in business and government, 2021)
HEI in India is plagued by many problems, one of the most noticeable being the high rate of attrition and turnover. While several factors account for turnover, one of the reasons for most employees is the lack of identification and belongingness with their institutions. The affection, however, does not evolve in a day and requires perennial nurturing from transformational leaders. Transformational Leaders pervade a feeling of belongingness among employees for their organization through transcendence of employees’ personal interests for organizational interests. The relationship between Transformational Leaders and Affective Commitment, though, is not necessarily linear or direct and can be better understood through identification of mediating variables. The present study assumes that perception of followers about characteristics of their job (JC) is the key psychological instrument in explaining relation between Transformational Leadership (TL) and Affective Commitment(AC).